Phenotypic and genomic analysis of isopropanol and 1,3-propanediol producer Clostridium diolis DSM 15410 - Sedlar, Karel; Vasylkivska, Maryna; Musilova, Jana; Branska, Barbora; Provaznik, Ivo; Patakova, Petra (Genomics (San Diego, Calif.), 2021)
Clostridium diolis DSM 15410 is a type strain of solventogenic clostridium capable of conducting isopropanol-butanol-ethanol fermentation. By studying its growth on different carbohydrates, we verified its ability to utilize glycerol and produce 1,3-propanediol and discovered its ability to produced isopropanol. Complete genome sequencing showed that its genome is a single circular chromosome and belongs to the cluster I (sensu scricto) of the genus Clostridium. By cultivation analysis we highlighted its specific behavior in comparison to two selected closely related strains. Despite the fact that several CRISPR loci were found, 16 putative prophages showed the ability to receive foreign DNA. Thus, the strain has the necessary features for future engineering of its 1,3-propanediol biosynthetic pathway and for the possible industrial utilization in the production of biofuels.
Keywords: Biofuels; Phylogeny; Clostridium; propylenglykoly; fenotyp; Phenotype; 2-propanol; fylogeneze; Industrial Microbiology; Propylene Glycols; biopaliva; 2-Propanol; Genome, Bacterial; průmyslová mikrobiologie; genom bakteriální